The Effect of Smart Pinwheel Games on the Ability to Recognize Numbers in Children Aged 5-6 Years at TK Negeri Pembina 1 Medan T.A 2022/2023 - Yuni Yuspita Sari; Aman Simaremare (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect of the smart wheel game tool on the ability to recognize numbers in children aged 5-6 years at TK Negeri Pembina 1 Medan. This type of research is experimental research with a Pre-Experimental Design, in the form of a One-Group Pretest-Posttest Design. The population in the study were 5 class B, then the sample for this study used a non-probability sampling technique. The sample in this study were Kindergarten B children, totaling 16 people. Data collection using the instrument sheet. The data analysis technique uses non-parametric statistics with a sample sign test ≤ 25. The test results show that the APE of the smart wheel has a significant effect on the ability to recognize numbers in children with the criteria of testing the hypothesis if H0 is accepted 0.05≤ probability of sample results, H0 is rejected if 0 .05 > sample outcome probability. The results of the hypothesis test are 0.05> 0.0021, it is proven that H0 is rejected, meaning that there is a significant increase in the child's ability to recognize numbers before and after treatment using the APE smart wheel. Thus it can be concluded that there is a significant effect of the use of the smart wheel APE on the ability to recognize numbers in children aged 5-6 years at TK Negeri Pembina 1 Medan T.A 2022/2023. Based on the results of this study, it is suggested for PAUD teachers to be able to use the smart wheel APE in introducing numbers to children.